Incidence and predictors of type 1 diabetes among younger adults aged 20–45 years: The diabetes in young adults (DiYA) study. (January 2021) - Lawrence, Jean M.; Slezak, Jeff M.; Quesenberry, Charles; Li, Xia; Yu, Liping; Rewers, Marian; Alexander, Janet G.; Takhar, Harpreet S.; Sridhar, Sneha; Albright, Ann; Rolka, Deborah B.; Saydah, Sharon; et al.
Abstract: Aims: To estimate incidence of type 1 diabetes (T1D) and to develop a T1D prediction model among young adults. Methods: Adults 20–45 years newly-diagnosed with diabetes in 2017 were identified within Kaiser Permanente's healthcare systems in California and invited for diabetes autoantibody (DAA) testing. Multiple imputation was conducted to assign missing DAA status. The primary outcome for incidence rates (IR) and the prediction model was T1D defined by ≥1 positive DAA. Results: Among 2, 347, 989 persons at risk, 7862 developed diabetes, 2063 had DAA measured, and 166 (8.0%) had ≥1 positive DAA. T1D IR (95% CI) per 100, 000 person-years was 15.2 (10.2–20.1) for ages 20–29 and 38.2 (28.6–47.8) for ages 30–44 years. The age-standardized IRs were 32.5 (22.2–42.8) for men and 27.2 (21.0–34.5) for women. The age/sex-standardized IRs were 30.1 (23.5–36.8) overall; 41.4 (25.3–57.5) for Hispanics, 37.0 (11.6–62.4) for Blacks, 21.4 (14.3–28.6) for non-Hispanic Whites, and 19.4 (8.5–30.2) for Asians. Predictors of T1D among cases included female sex, younger age, lower BMI, insulin use and having T1D based on diagnostic codes. Conclusions: T1D may account for up to 8% of incident diabetes cases among young adults. Follow-up is needed to establish the clinical course of patients with one DAA at diagnosis.